Reduced white-matter integrity and lower speed of information processing in adolescents with mild and moderate neonatal hypoxic-ischaemic encephalopathy. (September 2020) - Gosar, David; Tretnjak, Vali; Bregant, Tina; Neubauer, David; Derganc, Metka
Abstract: Introduction: Studies have shown that adolescents with moderate hypoxic-ischaemic encephalopathy (HIE) may have specific cognitive deficits, especially reduced speed of information processing. The aim of our study was to confirm these earlier findings find out whether the degree of impairment in speed of information processing correlates with the degree of white-matter impairment as measured by diffusion tensor imaging (DTI). Methods: Thirty-three participants (mean age 18y 5mo, SD 12mo; 19 male) with mild or moderate HIE and 32 neurotypical adolescents (mean age 17y 10mo, SD 12mo, 18 male) completed a comprehensive neuropsychological battery measuring short-term memory, inhibition, speed of information processing, long-term visual and verbal memory. Fourteen participants also underwent structural MRI and DTI scans. Results: After controlling for age, gender and maternal education we found a significant effect of HIE on speed of information processing ( F (2, 64) = 3.51, p < .037, η 2 = 0.115), but not on other neuropsychological domains. Using tract-based spatial statistics we were also able to confirm a correlation between the degree of impairment in this cognitive domain and fractional anisotropy in several white-matter tracts. Conclusions: The long-term cognitive outcome of moderate HIE includes reduced speed of information processing and is in part mediated by reduced integrity of major white-matter tracts. Highlights: Adolescent with mild and moderate neonatal HIE have reduced speed of information processing. Speed of information processing in adolescents with HIE is correlated with DTI measures of white-matter integrity. Neonatal DTI may help confirm the long-term impact of neonatal interventions for HIE (i.e. hypothermia) on cognition.